Gender and Power Dynamics of Social Relationships Shape Willingness to Participate in Biomedical HIV Prevention Research Among South African Adolescents and Young Adults - Closson, Kalysha; Lee, Laura; Dietrich, Janan J.; Beksinska, Mags E.; Hornschuh, Stefanie; Smith, Patricia; Smit, Jenni A.; Ndung'u, Thumbi; Brockman, Mark; Gray, Glenda; Kaida, Angela (Frontiers in Reproductive Health, 2021)
Background Understanding young women and men’s perceived barriers and facilitators to participation in biomedical HIV prevention trials is important for designing youth friendly services (YFS) and acceptable technologies, which are necessary for preventing high sustained HIV incidence in South Africa. This study explores the multileveled barriers and facilitators to young men and women’s willingness to participate in hypothetical biomedical HIV prevention research. Methods Eight age- (16-18 years and 19-24 years) and gender-stratified focus group discussions (FGDs) were conducted using semi-structured interview guides to explore young South African women and men’s willingness, perceived barriers, and facilitators to participating in biomedical HIV prevention research. FGD transcripts were uploaded to NVivo and coded collaboratively with youth study team members. Thematic analysis using Bronfenbrenner’s ecological model (individual, inter-personal, community, and societal) was used to guide a deductive coding procedure, which was documented and compared by gender. Results Thirty-one participants from Durban and 34 from Soweto participated in FGDs. Individual facilitators for participation were discussed more by young men and included financial incentives and altruism. Concerns about side effects of biomedical products were a common barrier. Interpersonal relationships with peers, intimate partners and caregivers influenced young people’s willingness to participate in HIV prevention research, more so among young women. For young women, gendered power dynamics and distrust of intimate partners and parents influenced both communication regarding participation and willingness to participate in research that is often stigmatized, due to societal norms around women’s sexuality. On a societal level, participants expressed distrust in medical and research institutions, however a sense of community that was developed with the study staff of this project, was a motivator to participate in future studies. Discussion At each level of the ecological model, we found participants expressed gendered barriers and facilitators for participation. Gender norms as well as distrust of partners, parents, and health care professionals were key barriers that cut across all levels. At each level participants discussed facilitators that were youth-engaged, underscoring the need to implement YFS, establish trust and address gender inequities within future biomedical HIV prevention studies wishing to engage and retain South African youth.